AN EMPIRICAL INVESTIGATION OF ICTS IN THE AGRICULTURAL DEVELOPMENT OF THE UNION TERRITORY OF PUDUCHERRY, INDIA - Sankaran, A.; Rajkumar, P. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
It is globally accepted that the agricultural sector is the backbone of every economy. This sector plays a significant role over the course of economic development by contributing a considerable share in the gross domestic product and employment generation. Further, this sector is considered as a herculean weapon to eradicate extreme poverty, food insecurity and poor standard of living particularly in the underdeveloped and developing nations. There are some internal and external forces which have both positive and negative effects on this sector, which includes government policies, environmental condition, population pressure on land, cropping pattern, globalization, international trade and information, communication and technology. Against the above theoretical background, the present study tries to assess the role of ICTs in the development of agriculture in the Union territory of Puducherry, India. In order to execute this study, both primary and secondary data have been used. Secondary data have been collected from the published reports and materials while primary data have been collected from 90 sample respondents from three villages using simple random sampling method. The dataset include socio-economic profiles of the sample respondents and role of television, radio, cell phone, news papers and internet in offering information for the development of agriculture. The study uses simple percentage and Garrett Ranking method to analyze the data. The result of this study shows that television is in the towering position, followed by radio, news papers, cell phone, and internet in generating awareness on suitable input applications like pesticide and fertilizer use, soil quality test, credit opportunities, agricultural prices and cultivation methods. Hence, the study suggests that agro-based programmes should be more effectively relayed through local and national level channels in vernacular language to enhance the agricultural production and productivity.